Factors that Influence the Withdrawal of Life Support in Nigeria: A Study in the Context of Religious Moral and Medical Ethics - Halim, R.; Yusof, Y.; Salihu, S. I. (International Journal of Psychosocial Rehabilitation, 2020)
The debate has been ongoing about the moral, religious and ethical implication of active and passive euthanasia. Active euthanasia is where drugs or injections are used by doctors to hasten or terminate the life of their patient. Passive euthanasia, on the other hand, is withholding or withdrawing of life-saving treatment. to end the life of a patient. Many see the former as more unethical and immoral, while others see both as having the same moral and ethical implication. An interview was conducted to investigate the practice of euthanasia via withdrawal of life support in Nigeria. Purpose: The aim is to see what are the factors that influence the practice of active and passive euthanasia. The practice of euthanasia is illegal under the Nigerian law, but some factors may be responsible for practicing it. Methodology: Qualitative data is used to investigate the practice in Nigeria. A semistructured interview is conducted with about six medical doctors in Nigeria. No more doctors were needed because saturation level was reached. The interview was audiotaped and transcribed without software aid because the respondents are not too many and the themes are limited. The research was approved by the Ethics Committee of the Aminu Kano Teaching Hospital in Nigeria. Result: In the research, it was found that doctors do not support the practice of euthanasia because of religious reason, but they tolerate passive euthanasia because of necessity especially the withdrawal of life support where a case is hopeless or due to limited facilities in the Intensive Care Unit. This is where there is the presence of a patient with reversible pathology. Conclusion: Nigerian doctors see active euthanasia as more unethical and immoral than passive euthanasia and the factors that influence it are rational.